Factors associated with stunting in Indonesian toddlers: the role of immunization and exclusive breastfeeding in Serang, Indonesia - Prihayati; Ismarina; Sadya Bustomi (Nursing and Health Sciences Journal (NHSJ), 2025)
Stunting remains a major public health problem in Indonesia, particularly in peri-urban and high-burden areas. Inadequate infant feeding practices and incomplete immunization are recognized as modifiable determinants of chronic undernutrition, yet local evidence examining their association with stunting is limited. This study examined the association between basic immunization status and exclusive breastfeeding with stunting among toddlers in Cilowong Subdistrict, Serang Regency, Indonesia. A quantitative cross-sectional study was conducted among 100 toddlers aged 6–59 months selected through simple random sampling from the local Posyandu registry. Data were collected between February 2025 using structured interviews with mothers or primary caregivers and standardized anthropometric measurements. Stunting was defined as height-for-age Z-score (HAZ) < −2 SD based on WHO Child Growth Standards. Immunization status was verified using the child’s KMS and health center records, while exclusive breastfeeding was assessed through maternal report. Data were analyzed using descriptive statistics and chi-square tests to calculate prevalence ratios (PR) with 95% confidence intervals (CI). The prevalence of stunting was 66.0%. Incomplete basic immunization was found in 63.0% of children, and only 15.0% had received exclusive breastfeeding. Incomplete immunization was significantly associated with stunting (PR = 5.05; 95% CI: 2.07–12.32; p = 0.001), as was non-exclusive breastfeeding (PR = 11.46; 95% CI: 2.95–44.41; p < 0.001). Incomplete immunization and lack of exclusive breastfeeding are strongly associated with stunting, underscoring the need for integrated community-based interventions through primary health care services.